The Effect of Country of Origin on Mobile Buying Behavior of Consumers: A Case from Pakistan (Global Journal of Management and Business Research, 2016)
The study aims at investigating country of origin effects on mobile phone buying behavior of consumers. The construct of Country of origin is studied in terms of brand image and Technological innovation in order to have in-depth insights. The survey technique based on questionnaire is used to collect data from 200 mobile phone users in large cities of Pakistan. We retrieved 175 valid questionnaires; the effective rate was 89%. Then the research was used descriptive statistical analysis on the sample data. Finally, the study regards consumer behavior as dependent variable and independent variables include country of origin, product knowledge and Ethnocentrism. The correlation analysis was used to analyze the relationship between consumer behavior and country of origin, product knowledge and Ethnocentrism. The results show that Country of origin in terms of "Brand image" and "Technological innovation" has positive impact on buying behavior of Pakistani Consumers while purchasing mobile phones. The high income class of Pakistani consumers is so strongly influenced by the Country of image in terms of "technological innovation "and "brand image" but with low income Pakistani consumers are strongly influenced by ethnocentrism (buy their own country's mobile phone).
Keywords: country of origin; customer satisfaction; pakistan; mobile phones; product knowledge